A comparative study on the performance of liquid flat-plate solar collector with a new V-corrugated absorber. (15th March 2019) - Fan, Man; You, Shijun; Gao, Xinlei; Zhang, Huan; Li, Bojia; Zheng, Wandong; Sun, Leizhai; Zhou, Tingting
Highlights: A new V-corrugated absorber with multi-channels is presented in this study. The optical/thermal efficiency of the new collector are increased by 15.8%/10.7%. The pump power consumption of the new collector is lowered by about 73%. Effects of key parameters on the collector thermal performance are investigated. Abstract: In this study, a new V-corrugated absorber with multi-channels is presented and applied in the liquid flat-plate solar collector. The absorber is extruded with aluminium and specific triangular channels are directly formed to improve the solar absorptance, reduce the heat conduction thermal resistance and decrease the pressure drop. Optical and heat transfer models for the new collector and a conventional sheet-and-tube collector are developed and experiments are carried out to validate the accuracy. Performance of the new and conventional collector are compared under different operational conditions and the results indicate that: (i) The daily average optical/thermal efficiency of the new and conventional collector are about 84.9%/69.4% and 69.1%/58.6%, respectively. (ii) The average exergy efficiency of the new and conventional collector are about 3.8% and 3.3% respectively under the mass flow rate of 10–90 g/s. (iii) The pressure drop and pump power consumption of the conventional collector are about 4.1 times higher than those of the new collector. The designing of V-corrugated absorber can improve the collector optical and thermal efficiency, and reduce the pressure drop and pump power consumption significantly, but exerts little effect on the exergy efficiency. Notwithstanding so, the performance improvement potential of the V-corrugated absorber is huge and the designing and manufacturing of the collector can be further developed.